Life-Long Learning for Enhancing Employability in the Age of Sun Rising Technologies - Waghodekar, P. H. (Journal of Engineering Education Transformations, 2006)
In this paper, it is argued that judicious adoption of the life-long learning (LLL) concept can enhance the potential and employability of young men in the age of sun rising technologies. The concept of LLL as envisaged by the ancient Indian rishis and as perceived by the Western world is presented. SUI! rising technologies are market driven with a global dimension. To meet this challenge, the developed countries have been working 011 LLL since the last three decades. Therefore, the LLL experiences of the Western world will be of immense use, in the ICT and globalisation age, to the developing countries like India. However, the LLL program as implemented in the ancient India, especially during the Vedic period, through Gurukul system, is much more encompassing than that as being followed by the Western countries today. India can achieve the ultimate goal set for LLL only via the Western route because of obvious reasons. It is stressed that India must have a national strategy and policy for LLL. India is already far behind the develop-ed countries and the gap is widening day by day. Th e challenges of the SUI! rising technologies and life-long learning, therefore, need to be addressed with true perspective; or else once more the train is missed.